2016
DOI: 10.1007/978-3-319-43580-0_6
|View full text |Cite
|
Sign up to set email alerts
|

HPV-Related Head and Neck Squamous Cell Carcinomas

Abstract: Since more than 5 years, it becomes evident that there is a new group of patients with squamous cell carcinomas of the head and neck area, namely human papillomavirus (HPV)-related (caused) tumors. As clinical statistics indicate, those patients have better prognosis, even despite more advanced stage compared to those with HPV-negative tumors. In fact, as a surrogate of HPV infection for clinical studies, an immunohistochemical expression of p16 protein is used. In the following chapter, the spectrum of squamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Compared with HPV-negative HNSC, HPV-positive HNSC represents a distinct subset that responds better to concurrent chemo-radiation and is related to better prognosis, with distinct genomic features. 49 , 50 High LIMA1 expression might indicate an adverse outcome in patients with HNSC. A previous study demonstrated that TP53 mutation was capable of regulating LIMA1 at transcription level, and TP53 mutations account for the downregulation of LIMA1 associated with poor survival of patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with HPV-negative HNSC, HPV-positive HNSC represents a distinct subset that responds better to concurrent chemo-radiation and is related to better prognosis, with distinct genomic features. 49 , 50 High LIMA1 expression might indicate an adverse outcome in patients with HNSC. A previous study demonstrated that TP53 mutation was capable of regulating LIMA1 at transcription level, and TP53 mutations account for the downregulation of LIMA1 associated with poor survival of patients with cancer.…”
Section: Discussionmentioning
confidence: 99%